Measurement and evaluation in human performance - Morrow, James R. Jr. 1947-; Mood, Dale; Disch, James G. 1947-; Kang, Minsoo (Champaign, IL Human Kinetics, 2016)
Measurement and Evaluation in Human Performance, Fifth Edition With Web Study Guide, leads students through the fundamentals of collecting and analyzing data of human performance and applying their results to real-life situations. Focusing on the core concepts of reliability and validity of data, the text provides all the necessary tools for evidence-based decision making that can be applied to physical therapy, allied health professions, kinesiology, sport and exercise science, physical education, health, and fitness.
Concepts in tests and measurements -- Using technology in measurement and evaluation -- Descriptive statistics and the normal distribution -- Correlation and prediction -- Inferential statistics -- Norm-referenced reliability and validity -- Criterion-referenced reliability and validity -- Developing written tests and surveys -- Physical fitness and activity assessment in adults -- Physical fitness and activity assessment in youth -- Assessment of sport skills and motor abilities -- Psychological measurements in sports and exercise -- Classroom grading : a summative evaluation -- Performance-based assessment : alternative assessments for measurement and evaluation
Preceded by Measurement and evaluation in human performance / James R. Morrow Jr. ... [et al.]. 4th ed. c2011.
Includes bibliographical references and index.
Keywords: Physical Fitness -- Testing; Athletic ability -- Testing -- Data processing; Athletic ability -- Testing -- Methodology; Sports -- Pyschological aspects -- Testing